An Algorithm of Faulty Antenna Location Based on Interval Analysis of Horizontal Beam-Width - Zhuoyi Tang; Zhidong Hu; Gang Lin (Dianxin kexue)
The problems such as decrease of antenna gain,the leakage of side-lobe signal,and the degradation of front-to-back ratio,were mainly discussed,and an algorithm of faulty antenna location based on interval analysis of horizontal beam-width was proposed,by dividing the horizontal beam-width with different radiation angle:±[0,15°],[16°,30°],[31°,60°],[61°,90°],[91°,120°],[121°,150°],[151°,180°].At last,through relational analysis of Rxqual,Rxlev,over-coverage index,and communication distance in different radiation angle interval,the location of faulty antenna was realized.